2017
DOI: 10.1213/ane.0000000000001546
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Phenotypes of Obstructive Sleep Apnea: Applications in Anesthesia, Surgery, and Perioperative Medicine

Abstract: Obstructive sleep apnea (OSA) is a prevalent sleep-disordered breathing with potential long-term major neurocognitive and cardiovascular sequelae. The pathophysiology of OSA varies between individuals and is composed of different underlying mechanisms. Several components including the upper airway anatomy, effectiveness of the upper airway dilator muscles such as the genioglossus, arousal threshold of the individual, and inherent stability of the respiratory control system determine the pathogenesis of OSA. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
60
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 124 publications
(60 citation statements)
references
References 125 publications
0
60
0
Order By: Relevance
“…OSA has many endotypes and phenotypes. 24 In patients with OSA, opioids attenuate the arousal response to hypoxia and prolongs airway obstruction. 25 26 The physiological phenotype of OSA with a high arousal threshold may be more sensitive to the sedative effects of opioids and anaesthetic drugs.…”
Section: Discussionmentioning
confidence: 99%
“…OSA has many endotypes and phenotypes. 24 In patients with OSA, opioids attenuate the arousal response to hypoxia and prolongs airway obstruction. 25 26 The physiological phenotype of OSA with a high arousal threshold may be more sensitive to the sedative effects of opioids and anaesthetic drugs.…”
Section: Discussionmentioning
confidence: 99%
“…As there is still no consensus regarding standardized diagnostic criteria for OSA, with AHI cut-off criteria considered an interim standard 101 , many researchers regard OSA as a heterogeneous disease in terms of symptoms, etiology, comorbidities and outcomes. At present, factors including AHI, EDS, sex, age, obesity and race/ethnicity are all recognized as phenotypes or important factors impacting OSA 102 , 103 . Our study demonstrated that these phenotypes based on clinical or demographic information had both significant (e.g., age and sex) and non-significant (e.g., AHI and ODI) relationships with GMV.…”
Section: Discussionmentioning
confidence: 99%
“…bstructive sleep apnea (OSA) is the most common type of sleep-disordered breathing and is characterized by cyclical alterations between pharyngeal collapse and arousals during sleep. 1 Consequently, there are recurrent episodes of nocturnal hypoxemia, hypercapnia, endothelial dysfunction, hypercoagulability, and sympathetic overactivity. 2 In the general population, OSA is associated with higher risk of cardiovascular complications 3 such as hypertension, 4 myocardial ischemia, heart failure, 5 arrhythmias, stroke, 6 and sudden cardiac death.…”
mentioning
confidence: 99%
“…7 General anesthetics, sedatives, and postoperative analgesics are potent respiratory depressants that relax the upper airway dilator muscles and impair ventilatory response to hypoxemia and hypercapnia. 1 Each of these events exacerbates OSA and may predispose patients to postoperative cardiovascular complications. In this respect, perioperative mismanagement of OSA has led to serious medicolegal consequences.…”
mentioning
confidence: 99%